Överdrivet alarm eller ödesdiger influensa: En studie av nyhetsrapporteringens (re)produktion av betydelser om influensapandemier - Ljuslinder, Karin (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2015)
Media reporting plays a key role in the general public’s perception of the risk of pandemics. The majority of Swedes have never had a pandemic flu. Instead they recieve their experiences and opinon from news media. The public cannot take for granted that the news mirror the spread and risks with a flu. Media are guided by other principles than retelling an event. Ownership, finances and media logic are some of the variables that determine media content. This study examines with the discourse analytical tool of articulation, how historic pandemics have been represented in a printed daily news press (Dagens Nyheter), the only Swedish news medium that has been active during the entire studied time period, 1898–2009. The aim is to contribute to better understanding of how media logic and other guiding variables shape content and thereby have an impact on cultural meanings and notions. The result shows that the representation has moved from reports of an uncontrollable force of nature (1898) to medical science and society’s control (1969) and, in 2009, back to reports about the swine flu as an apocalyptic catastrophe. One possible explanation can be that different variables are governed by different, and, competing interests. Even if the reporting is alarmistic both in 1898 and 2009, the reasons may differ. This study shows the effect on the pandemic reporting when the news medium balances between being a democratic information channel and a market economic business.